Reef: Retainable evaluator execution framework - Weimer, Markus; Curino, Carlo; Ramakrishnan, Raghu; Rao, Sriram (Proceedings of the VLDB Endowment, 2015)
Apache REEF™ (Retainable Evaluator Execution Framework) is a library for developing portable applications for cluster resource managers such as Apache Hadoop™ YARN or Apache Mesos™. Apache REEF drastically simplifies development of those resource managers through the following features: